Characteristic and effect analysis of protein and peptide in Cantonese cured meat processing - Zhi Qu; Chunqian Feng; Ruiling Li; Nan Liu; Shanqing Zheng (Food Science and Human Wellness)
The aim of this work was to explore the physicochemical and structural properties, lipid oxidation and antioxidant capacity of the peptides extracted from Cantonese cured meat and as well as to investigate the effect of drying time on the sarcoplasmic and myofibrillar proteins of Cantonese cured meat. The results suggested that salting out, protein oxidation and heat treatment were closely related to surface hydrophobicity and the secondary structure of peptides was changed by processing. And the peroxide value and the value of tributyltin compounds were different in evaluating the degree of lipid oxidation. Glu and His were the major amino acid. The approximate molecular weights of the sarcoplasmic proteins and myofibrillar proteins ranged from 31 kDa to 50 kDa and 66 kDa, respectively. The results indicated that reducing the levels of protein oxidation and improvement of the antioxidant properties should be of great interest to preserve the nutritional quality of meat products and prolong preservation period.